NAVIGATING THE DIAGNOSTIC CHALLENGES OF CALCIPENIC RICKETS COMPLICATED BY HYPERCOAGULATION, HYPOKALEMIA, AND SECONDARY AMENORRHEA IN A 21-YEAR-OLD FEMALE - Sipayung, Merylla Filianty; Anggraini, Ratna Maila Dewi; Shahab, Alwi; Kusnadi, Yulianto; Syahrir, Mediarty; Partan, Radiyati Umi (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Rickets, a metabolic bone disorder primarily attributed to insufficient mineralization of the epiphyseal plate or osteoid calcification failure due to vitamin D or calcium deficiency, encompasses a spectrum of etiological factors including genetic anomalies and drug-induced manifestations. This report details a case of calcipenic rickets in a 21-year-old Indonesian female who presented with growth retardationand leg deformities since age 13. Extensive evaluation revealed hypocalcemia, hyperparathyroidism, elevated alkaline phosphatase, reduced phosphate levels, and decreased vitamin 25(OH)D concentrations. Alongside calcipenic rickets, the patient exhibited hypercoagulability, hypokalemia, and secondary amenorrhea. Treatment comprised Vitamin D supplementation (5000 IU) and calcium supplementation. Early diagnosis, guided by history, physical examination, and laboratory and radiological assessments, is essential. The profound impact of rickets on stature and bone structure underscores the urgency of timely diagnosis and appropriate intervention to ensure optimal outcomes for affected individuals.